고관절 잠행 골절로 진단된 환자의 임상적 특징 - 유욱현; 김혜진; 조석진; 오성찬; 강태경; 최승운; 류석용; Yu, Wookhyun; Kim, Hyejin; Cho, Sukjin; Oh, Sungchan; Kang, Taekyung; et al. (Daehan oe'sang haghoeji, 2013)
Purpose: This study was undertaken in order to identify the characteristics of patients diagnosed with occult an hip fracture after hip trauma. Methods: We retrospectively reviewed the medical records and radiology reports of all patients who underwent hip skeletal computed tomography (CT) for suspected hip fractures but had normal initial X-rays after hip trauma between August 2006 and January 2012. The variables evaluated included age, gender, body mass index (BMI), accident mechanism, previous fracture, independence, late presentation, ability to bear weight, pain on passive rotation, tenderness of the groin area, diagnosis and treatment. Patients were divided into two groups, with hip fracture (occult hip fracture group) and without hip fracture (no fracture group) to evaluate the characteristics associated with an occult hip fracture. Results: The patients, a total of 139, had a mean age of 58.3 years and included 72 male patients(51.8%). The occult hip fracture group included 43 patients(30.9%). Of those 43, 21 patients(48.8%) had intertrochanteric or trochanteric fractures, 8 patients(18.6%) had femur neck fractures and 14 patients(32.6%) had acetabular fractures. Of the 43, 15 patients(34.9%) needed operative treatment. Age was higher in the occult hip fracture group than it was in the no fracture group($64.4{±}19.1$ years vs. $55.5{±}23.6$ years, p=0.021). A previous fracture was associated with the presence of a new fracture (p=0.014; OR=3.971, 95% CI=1.314-11.997). Conclusion: Further evaluation of patients who are older or have history of fractures is prudent, even though the initial X-rays are normal.